PENYAMAKAN KULIT IKAN NILA (Oreochromis sp.) DENGAN PERLAKUAN PEMUCATAN (BLEACHING) MENGGUNAKAN PEROKSIDA - Nurul Hak (Jurnal Perikanan Universitas Gadjah Mada, 2013)
Research for tanning ﬁsh skin nile (Oreochromis sp.) on bleaching treatment has been done. Concentration of peroxide as bleaching agent variated in 2, 4, and 6% (v/w) and non bleaching process as a control. As a nile Leather product research characterized trough physic parameter, chemical and organoleptic analysis. Result of nile leather product the optimal amount of peroxide was 4% which resulted in tensile strength of 205 kg/cm2, elongation of 84,67%, sewing strength of 117,29%, and rigid temperature of 84oC. Chemical properties for the 4% peroxide were 14.99% of water content, 1.65% of chrome content, 2.25% of ash content, and 12.90% of lipid content. Sensory analysis shows that nile leather in the same variable (4% peroxide) has smooth surface that most panelist valuated and it has scale tissue unique motif, shinning surface, elastic, soft, and meatless. The colour of scale tissue was a soft dark, but the most of panelist choose nile ﬁ sh leather with 6% peroxide bleaching treatment.